Minimally invasive surgery for esophageal cancer – benefits and controversies - Wallner, Grzegorz (Kardiochir Torakochirurgia Pol, 2014)
Open esophagectomy (OE) requires extensive surgery and is associated with significant morbidity and mortality. Furthermore, the long-term results of esophageal cancer surgery are not satisfactory; hence, the best surgical approach is constantly under debate. During the last twenty years, minimally invasive esophagectomy (MIE) employing laparoscopy and/or thoracoscopy has been introduced in a growing number of centers worldwide. To date, several studies have demonstrated that MIE has better outcomes than OE, as it results in shorter hospital stay and decreased overall morbidity. However, the length of operating time in MIE is increased in comparison to OE. The survival benefit has been demonstrated to be similar in OE and MIE. Highly advanced laparo-thoracoscopic skills are required to perform MIE; along with the relatively long learning curve, this makes MIE feasible only in high-volume, experienced university surgical centers. There is a need for further large-scale comparative studies to prove the superiority of MIE over open surgery.